Handbook of diversity in feminist psychology - Landrine, Hope, 1954-; Russo, Nancy Felipe, 1943- (Springer, 2010)
Critical for all those who are in the field of psychology to own, refer to, and use. No longer are diversity and gender issues considered to be on the periphery as they once were ... one would be remiss in not considering these factors in psychology. -- Florence L. Denmark, PhD (From the Foreword). Author, Psychology of Women. This handbook presents a multicultural approach to diversity in feminist psychology. Provocative and timely, the text comprehensively discusses the cutting-edge of feminist discourse, covering major topics such as multicultural feminist theory, gender discrimination, agin.